Mono‐ and Di‐chloro‐bridged Discrete Dimers and Trimers and Mono‐Chloro‐Bridged 1D‐Coordination Polymer of Copper(II). Magneto‐structural Studies12. Issue 6 (7th March 2014) - Singh, Ravindra; Lloret, Francesc; Mukherjee, Rabindranath
Abstract The synthesis, structural characterization, and magnetic properties of three copper(II) complexes, a mono‐chloro‐bridged [Cu2II(L6)2(μ‐Cl)(Cl)(CuIICl4)] (1) and a dichloro‐bridged [CuII2(L7)2(μ‐Cl)2][ClO4]2 (3) discrete trimers and dimers, and a mono‐chloro‐bridged 1D‐coordination polymer [CuII(L6)(μ‐Cl)][ClO4]·CH3CN (2), are reported. Molecular structures were authenticated by X‐ray crystallography. Temperature‐dependent magnetic measurements carried out on powdered samples of 1–3 indicated a very weak antiferromagnetic exchange‐coupling within the CuII(μ‐Cl)CuII(μ‐Cl)CuIICl3+ units in 1 [Curie‐Weiss plot: θ = –0.19(1) K and g = 2.07(1)], a ferromagnetic behavior within CuII(μ‐Cl)2CuII2+ units in 3 [Ĥ = –JS1·S2: J = +6.0(1) cm–1, D (zero‐field splitting parameter) = 4.5(2) cm–1, and g = 2.11], and a weak intrachain antiferromagnetic behavior due to CuII(μ‐Cl)CuII3+ units in 2 [single‐chain polymer: J = –0.20(1) cm–1 and g = 2.11]. The square‐pyramidal stereochemistry of the central copper(II) atoms in 1–3 was identified by their absorption spectral properties in acetontrile. An attempt was made to rationalize the observed magneto‐structural behavior.